Towards open access: managerial, technical, economic and cultural aspects of improving access to research outputs from the perspective of a library and information services provider in a research university - Pinfield, Stephen (2011)
For academic research to release its value, it has to be communicated. It is essential, if research is to flourish, that the various forms of research communication, including journal articles and similar research outputs, are as easily and widely available as possible. The publications in this submission, produced between 1998 and 2010, all discuss major aspects (managerial, technical, economic and cultural) of improving access to research outputs in order to support research activity in higher education institutions. The later works focus in particular on the issue of ‘open access’ (OA) publishing and dissemination.